PECULIARITIES OF FICTIONAL WORLD OF G. PAHUTYAK’S STORY “GENTLEMAN IN A BLACK SUIT WITH SHINY BUTTONS” - Sirenko, S. A. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In the article the specificity of the fictional world of G. Pahutyak’s story «Gentleman in a black suit with shiny buttons» is analyzed in the light of the approach of cognitiveanthropology. The narrative semantics is investigated, the attributes and intents of N-forces, motivational models of characters, features of their private worlds, focalization in the fictional world of story is highlighted.